Information-Theoretic Capacity of a Tetra-Stranded Hereditary Polymer : Effective Alphabets, Encoding Density, and Readout Constraints in Q-DNA - Barack Ndenga (Publisher, 2025)
The informational capacity of a hereditary polymer is constrained not only by its chemical alphabet but also by its structural organization and readout mechanisms. Canonical duplex DNA encodes information primarily through pairwise base complementarity, yielding well-characterized limits on information density and error tolerance. In this work, I develop an information-theoretic framework for Q-DNA, a canonical tetra-stranded hereditary polymer, and show that tetra-strand coupling enables non-pairwise, multi-body encoding schemes. I derive upper bounds on information per unit length under structural and readout constraints, compare Q-DNA to DNA, RNA, and XNA systems, and identify regimes in which tetra-stranded heredity may trade encoding density for robustness—or vice versa. This analysis renders Q-DNA information capacity quantitatively testable and places tetra-stranded heredity within a rigorous communication-theoretic framework.
The capacity of a hereditary polymer to encode information is constrained not only by its chemical alphabet, but also by its structural organization, replication noise, and readout mechanisms. Canonical duplex DNA encodes information primarily through pairwise base complementarity, leading to well-established limits on information density and error tolerance. However, this pairwise paradigm represents only one point in a broader design space of possible genetic systems. In this work, I develop an information-theoretic framework for Q-DNA, defined as a canonical tetra-stranded hereditary polymer, and investigate how tetra-strand coupling enables multi-body encoding schemes that are not reducible to pairwise base pairing. I derive upper bounds on information capacity per unit length under structural, topological, and readout constraints, and explicitly distinguish raw combinatorial capacity from usable information. I compare the encoding properties of Q-DNA with those of DNA, RNA, and xeno-nucleic acids (XNA), showing that Q-DNA introduces a new axis in genetic information design: increased encoding flexibility through multi-strand correlations rather than expanded chemical alphabets. This leads to distinct trade-offs between information density and robustness, with regimes in which tetra-stranded heredity may favor redundancy and error tolerance over maximal density, or conversely achieve higher effective alphabets at the cost of increased decoding constraints. Finally, I formulate falsifiable predictions concerning non-linear scaling of information with genome length, correlated error patterns across strands, and reader-limited capacity ceilings. By embedding tetra-stranded heredity within a rigorous information-theoretic framework, this work establishes encoding capacity as a decisive criterion for evaluating Q-DNA as a viable alternative genetic system and positions Q-DNA within the broader landscape of theoretical biology, synthetic genetics, and origin-of-life research.